The Role of Social Media in Fueling Resource-Based Conflict: A Case Study of Inter-Clan Conflicts in Somalia - Hassan, Bashir Said (Advances in Social Sciences Research Journal, 2025)
Social media has rapidly transformed the information landscape in Somalia, emerging as a potent tool in shaping inter-clan conflict dynamics, particularly in resource-scarce regions. The country, historically plagued by resource-based inter-clan conflicts over land, pasture, and water, now faces a digital dimension to its conflict landscape. Platforms such as Facebook, WhatsApp, TikTok, and Twitter have become central to clan mobilization, misinformation dissemination, and escalation of violence. The study explores how the proliferation of social media influences inter-clan conflicts in Somalia and the mechanisms communities and authorities use to respond. The devastating impact of misinformation and hate speech in a weak regulatory and low digital literacy environment has intensified clan polarization and conflict recurrence.